# math check my answers

posted by .

1. 2(x+3)squared-6x+5=0
Answer= 2xsquared+6x+23=0

2. 3xsquared-6x+5=-2(x+1)-10
Answer= 3xsquared-4x+17=0

How would I solve from this point?

• math check my answers -

squared= ^2

• math check my answers -

1. 2(x+3)^2-6x+5 = 0

(x+3)^2 = x^2 + 6x + 9

2x^2 +12x + 18 - 6x +5 = 0

Combine terms.

2x^2 + 6x +17 = 0

Unless you have a typo, I don't agree with your answer.

2. 3x^2 - 6x + 5 = 2x + 2 - 10

Combine terms.

3x^2 - 8x + 2 = 0

Remember that, if you subtract/add from one side, you have to do the same thing to the other side of the equation.

## Respond to this Question

 First Name School Subject Your Answer

## Similar Questions

1. ### algebra

y=3(x+5)(x-2) I'm suppose to simplify right?
2. ### Algebra 1

(3xsquared-8x+1)(-2xsquared+-2) (i wrotee squared because i don't know how to type an exponent) Please help me to understand the steps of this problem! I'm not sure if I add the exponents or multiply them...
3. ### algebra 2

SImplify the expressions. 1. x to the seventh times 1/x squared 2. (3 quaredx to the sixth)cubed 3. x to the nith/ x negitive squared 4. 15xsquaredy/ 6x to the fourthy to the fifth times 6xcubed y squared/5xy USE direct substitution …
4. ### geometry

solve for x: 3xsquared+5x=2
5. ### math

(3xsquared-7x-6)+(2xsquared-4x+1) simplify
6. ### Math

The question is simply and answer in standard form 3x2(that is x squared)-2x+1+x2(xsquared)+2x-9 so I made it 3xsquared+xsquared=4xsaqured -2x+2x=0 the answer is: 4xsquared-(-8)=4xsquared+8 Then it asks the type of polynomial?
7. ### math

3xsquared + 27 = 5 3xsquared -5x = -3xsquared + 6 SOLVE
8. ### Calculus

find an equation of the tanegent line to the curve 3xsquared + 5ysquared=8 at the point (1,1)
9. ### Intermediate Algebra

Please help with the below. I know the answer I need help figuring out how to get the answer I am obviously doing something wrong, because I come up with a different answer that what I am supposed to. Here it is: F(X)3Xsquared-5X+1 …
10. ### Math

solve for the vertex f(X) = (2x-2)squared -3xsquared +6 plss.. solve this for me deadline tomorrow in the afternoon.. need your help ma'am/sir.. thank you. :D

More Similar Questions